HPB P53 Outcomes after remnant cholecystectomy: is laparoscopic approach feasible?. (7th December 2022) - Ibrahim, Rashid; Abdalkoddus, Muhammad; Mownah, Omar A; chanthu, Aye; Yao, Lu; Aroori, Somaiah
Abstract: Background: Subtotal cholecystectomy (STC) is perceived as a safe approach in difficult cholecystectomies to prevent bile duct and vascular injury. However, the gallbladder remnant can become symptomatic, necessitating further surgical intervention. This study aims to evaluate the safety profile and peri-operative outcomes of remnant cholecystectomy (RC) Methods: We retrospectively reviewed the records of all patients that underwent STC from 2009 to 2019. Patients that underwent RC were included in the study. Results: We identified 97 STC patients during the study period. Of this cohort, 16 patients (16.5%) presented with symptoms attributed to remnant gallbladder. The median age of this group was 64 years [Inter quartile range (IQR) 54–69] with equal male to female distribution. The median body mass index: 31kg/m2 (IQR 28–33). Twelve patients then proceeded to RC. All cases were performed by a consultant Hepatobiliary surgeon in an elective setting. The median operative time was 88 minutes (IQR 80–96) with 67% completed laparoscopically. No patients suffered bile duct injury. Median hospital was 3 days (IQR 1–5). Readmission rate was zero. One patient suffered with post-op hypotension requiring inotropic support. Overall mortality is zero. At the end of the follow up period [median of 14 months (IQR 2–26)], 8 patients (67%) reported symptoms resolution. Conclusions: Remnant cholecystectomy is a safe operation that can be performed laparoscopically. It has a low complications rate and relatively short hospital stay when performed by an experienced surgeon. However, symptomatic resolution is not achievable in all cases.